Karakteristik Pembakaran Briket yang Terbuat dari Limbah Sabut Kelapa dengan Perekat Limbah Nanas Pada Berbagai Tekanan Pemadatan - Willyanto Anggono; Ivan Christian Hernando; Stevanus Yuke (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2026)
The use of biomass waste as an alternative energy source is an effective way to reduce dependence on fossil fuels and address environmental issues. This study analyzes the combustion characteristics of briquettes made from coconut coir waste using pineapple waste as a binder. The research methodology includes raw material drying, mixing with a 5% binder concentration, and briquette molding under compaction pressures of 1 MPa and 2 MPa. The parameters tested include calorific value, burning rate, ignition time, and flame temperature. The results indicate that these briquettes achieved a peak calorific value of 4606 kcal/kg, surpassing that of bintaro leaf waste briquettes (4164 kcal/kg). The application of 2 MPa pressure yielded the best performance, characterized by a longer combustion duration (1295 seconds) and temperatures reaching 600°C, though it required a longer ignition time than the 1 MPa variant. The denser structure resulting from increased compaction pressure was proven to enhance combustion efficiency and stability. The primary contribution of this research lies in the use of pineapple waste as an innovative organic binder, which has been proven to significantly increase the calorific value and combustion duration of biomass briquettes compared to conventional binders.